Special issue: The United Nations at 75 in Global Governance: A review of multilateralism and international organizations - Δικαίος Γιώργος (Ελληνική Επιθεώρηση Πολιτικής Επιστήμης, 2022)
Special issue: The United Nations at 75 in Global Governance: A review of multilateralism and international organizations Volume 26 (2020), Issue 2, pp. 199-358